Análisis de los efectos del establecimiento de judicaturas especializadas en materia constitucional en primera y segunda instancia para efectivizar garantías jurisdiccionales. - Guamán Cutiupala Marcia Verónica (2025)
This legal research paper examines the potential legal, institutional, and social effects derived from the governmental decision—endorsed by popular support—to establish specialized courts in constitutional matters at the first and second instance levels within the Ecuadorian state, with the aim of guaranteeing the protection of citizens' constitutional rights. Specifically, it seeks to make jurisdictional guarantees enshrined in the Constitution of the Republic of Ecuador more effective. Constitutional jurisdiction in the country faces a growing need to strengthen access to justice in matters of fundamental rights. This need has prompted the implementation of specialized bodies within the judicial system, whose purpose is not only to improve the efficiency and timeliness in resolving constitutional cases, but also to ensure that judicial decisions in this area strictly conform to constitutional principles and the protection of fundamental rights. From a doctrinal and normative perspective, this research analyzes judicial specialization in constitutional matters as a mechanism to strengthen the effective protection of fundamental rights, improve the quality and consistency of judicial decisions, and reduce interpretive dispersion in the adjudication of constitutional actions such as the Action for Protection, Habeas Corpus, Habeas Data, Action for Free Access to Public Information, Action for Non-Compliance, Extraordinary. The study also examines comparative experiences from other Latin American legal systems that have implemented specialized constitutional courts, as well as the rulings of the Constitutional Court of Ecuador, which have addressed the need for jurisdictional technical specialization to guarantee access to constitutional justice. 6 This research aims to analyze the extent to which judicial specialization seeks to improve the quality of jurisdictional protection of constitutional rights. It includes a normative review of the establishment and regulation of these bodies and offers a comparative analysis between the efficiency of specialized constitutional courts and traditional judicial units in resolving constitutional disputes. This comparison allows for an assessment of whether specialization has truly increased the effectiveness of rights protection. The study also explores the perceptions of justice system users and legal professionals regarding the implementation of specialized constitutional courts. Through interviews, it gathers insights on how these institutions are perceived and what expectations the public has regarding this state decision, particularly concerning the respect and effective protection of constitutional rights. The findings provide an objective perspective on the role of specialized courts in ensuring procedural agility and technical expertise. A key aspect of the analysis is the impact of specialization on the unification of jurisprudential criteria in matters of constitutional rights. Having judges and courts exclusively dedicated to this field enhances the consistency of rulings, thereby contributing to legal certainty and preventing contradictions in the interpretation of constitutional rights. Keywords: Specialized Courts, Constitutional Law, Jurisdictional Guarantees, Justice System, Legality.